Sub-acute and sub-chronic toxicity assessment of the antimicrobial peptide Dermaseptin B2 on biochemical, haematological and histopathological parameters in BALB/c mice and Albino Wistar rats - Abdille, Ahmed A.; Kitimu, Shedrack Reuben; Ndubi, Mark M.; Kimani, Josephine; Maina, Esther N.; Bulimo, Wallace; Gavamukulya, Yahaya; Wamunyokoli, Fred (Heliyon, 2022)
Dermaseptins (Drs) are peptides found in the skin secretions of a variety of Hylid frogs, particularly those belonging to the Agalychnis and Phyllomedusa families. Dermaseptin B2 (Drs B2), an amphipathic, α-helical polypeptide was reported as the most active of the Dermaseptin B family. We have previously shown that Drs B2 has strong anti-proliferative activities against RD cells in vitro and thus required further evaluations for future medical applications. Aim: The aim the study was to evaluate the 14-day sub-acute and 90-day sub-chronic toxicities Drs B2 in vivo. Materials and Methods: BALB/c mice were treated with increasing concentrations of 5–25 mg/kg of Drs B2. Rats were treated with 2, 4 and 10-fold concentrations of the calculated LD50 of Drs B2 following OECD recommendations. At the end of the experimentation periods, the animals were sacrificed and dissected to collect blood and selected organs for analysis of any effects caused by Drs B2 treatment on the biochemical, haematological, and histological parameters. Results: The 14-day sub-acute toxicity tests did not cause significant alteration in the biochemical, hematological and histological parameters. The 90-day sub-chronic toxicity study showed lower ALT and AST than control at doses 1.9 mg/kg and 4.6 mg/kg, respectively. Their haematology results also showed higher platelet count than the controls but the differences were not statistically significant. Histological analysis showed increased megakaryocytes in the spleen for both the mice and the rats. Conclusion: The results of this study indicate that short term treatment of Drs B2 could be safe to the animals, however, long-term treatment can have mild effects on the liver parameters and cause an inflammatory response in the spleen.
Keywords: Dermaseptin B2; Antimicrobial peptides; Toxicity; Sub-acute toxicity; Sub-chronic toxicity